Models of Revolutionary Action: The Kasama in Ang Bayan During the Anti-Dictatorship Struggle (1982-1985) - Mongaya, Karlo Mikhail I. (Archīum Ateneo, 2024)
This article discusses the concept of the kasama, or comrade, as articulated in Ang Bayan, the central organ of the Communist Party of the Philippines (CPP), in the years 1982 to 1985. Critically reading Ang Bayan articles and related archival material, I look into the concrete articulation of comradeship in the Philippine experience during the height of the anti-dictatorship struggle against the Marcos dictatorship. I underscore the way kasama becomes fully intelligible as a collective subjectivity among those engaged in revolutionary struggle in juxtaposition to the figures of the masses, allies, and enemies of the people. I contemplate how this concept of the kasama is translated into Ang Bayan articles that function to provide readers with models for the effective carrying out of revolutionary tasks. Of significance here is Edel Garcellano’s assertion on the need to read revolutionary writing beyond narrow dominant valuations grounded on illusions of neutrality and profit imperatives. While borne out of specific conditions framed by the exigencies of underground resistance against dictatorship, these revolutionary models not only give an understanding of the term kasama but promise a glimpse of the discursive operation of revolutionary journalism as a distinct genre.